FMS*CALCIUMFLUOR INCREASES ALKALINE PHOSPHATASE EXPRESSION DURING OSTEOGENESIS IN VITRO OF TIBIA-DERIVED RAT OSTEOBLASTS BY ACTIVATION OF Ga0/Gai PROTEINS - C. Palermo; P. Manduca (Journal of Biological Research, 2000)
FMS*Calciumfluor is a preparation developed with the rationale of resonance homeopathy according to the protocols of the German homeopathic p harmacopoea ( 1, 2) .